Research on the Weldability and Service Performance of 7075 Aluminum Alloy Welding Wire Prepared by Spray Forming–Extrusion–Drawing - Chunkai Zhou; Xiaoping Li; Gao Hua (Metals)
A large number of MIG welding tests were carried out on a 3 mm thick 7075 aluminum alloy plate prepared by the self-developed jet forming–extrusion–drawing process of 7075 high-strength aluminum alloy welding wire, and the welding process of the welding wire and the change in the performance of the welded joint after T6 heat treatment were studied. The results show that the self-developed wire has a good forming joint and a wide welding process window: the welding speed is 5–7 mm/s, and the welding current is 100–150 A. The main precipitated phases in the joint were η(MgZn2), S(CuMgAl2), Mg2Si, and Al13Fe4, which were continuously distributed at the grain boundaries in the form of coarse networks or long strips, which was an important reason for the weak performance of the joints. After the heat treatment of T6, the precipitated phase in the joint was greatly reduced, the element segregation phenomenon was improved, and the residual precipitated phase was mainly Al13Fe4 and a small amount of insoluble phase Fe and Si, and the recrystallization size of the heat-affected zone was refined. Through heat treatment, the average microhardness of the joint was increased from 110 HV to 150.24 HV, and the tensile strength was increased from 326 MPa to 536 MPa, reaching 97.5% of the strength of the base metal, indicating that the softening phenomenon was significantly improved after heat treatment, and the joint had excellent performance.